FAKTOR-FAKTOR PENENTU PROFITABILITAS BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2012-2015 - Haridha Meilia Rahayu; Faisal Faisal (Diponegoro Journal of Accounting, 2019)
This study aims to analyze integrity against profitability. To analyze the effect of capital adequacy on profitability. To analyze operational influence on profitability. To analyze the influence of the market on profitability. To analyze the effect of credit on profitability. To analyze the influence of the company on profitability.The research methodology is data analysis in this study which uses quantitative analysis. Quantitative analysis is done by collecting data and then processing it. The technical data used in this study is multiple linear regression.The results of the study and discussion are ROA by the sixth variable free of LDR, CAR, BOPO, NIM, NPL, and FIRM SIZE. While the rest of the words by other causes outside the model. From the calculation results, the F value is calculated significantly. This means that the value of the P value that shows the variables and LDR, CAR, BOPO, NIM, NPL, FIRM SIZE together have a significant effect on ROA. LDR variable is partial to ROA.